Risk factors for adverse pregnancy outcomes in women with intrahepatic cholestasis of pregnant women - Yu B Uspenskaya; A A Sheptulin; I V Kuznetsova; E P Gitel; N V Goncharenko; A N Gerasimov (IP Berlin A.V., 2018)
Intrahepatic cholestasis of pregnant women (ICPW) is associated with an increased risk of complications of pregnancy. Objective prognostic markers of adverse pregnancy outcomes except for a high level of bile acids (BA) in the mother's blood serum, exceeding 40 μmol/l, do not currently exist. However, the determination of the BA levels is not available in all laboratories, which indicates the need to search for other informative prognostic markers of complications of pregnancy in patients with ICPW. Objective: to determine the risk factors for adverse pregnancy outcomes in ICPW. Materials and methods. A prospective study included 97 pregnant women diagnosed with ICPW. The diagnosis was established with an increase in the serum level of the BA in excess of 10 μmol/l. Patients underwent clinical and laboratory examinations with assessment of biochemical markers of liver damage, antioxidant status (determination of superoxide dismutase, glutathione peroxidase, selenium, zinc level). Biochemical indices and severity of pruritus were assessed at the time of diagnosis of ICPW, after 1 and 2 weeks of treatment with ursodeoxycholic acid (UDCA) at a dose of 500 mg to 2 g per day. In the study of perinatal outcomes, the term of delivery, the method of delivery, the presence of signs of intrauterine fetal hypoxia, the state of the fetus at the time of birth were taken into account. Results of the study. In the observed group of patients, the incidence of preterm birth was 31.9%, intrauterine fetal hypoxia 29.9%, pre-eclampsia 23.7%, the need for a cesarean section due to the development of pregnancy complications arose in 40 (41.2%) cases. The risk factors for complications of pregnancy in patients with ICPW were: early onset and longer duration of ICPW, reactivation of cholestasis after its regression against the background of UDCA treatment and less effective treatment of skin itching in patients with manifest forms of ICPW. The laboratory markers of adverse pregnancy outcomes were a high level of maternal total serum BA and a low efficiency of its reduction against the background of treatment, a slow rate of decrease in hepatic transaminase activity against the background of treatment, a low level of antioxidant protection enzymes. The use of sex hormones during pregnancy promoted more frequent development of preeclampsia and increased the frequency of indications for cesarean delivery. The conclusion. Patients with early manifestation of ICPW and reactivation of cholestasis after its regression on the background of treatment, low effectiveness of treatment of pruritus, and also taking drugs of sex hormones require special attention and active management in connection with an increased risk of complications of pregnancy. It is advisable to carry out dynamic monitoring of the level of BA, hepatic transaminases and antioxidant enzymes in dynamics against the backdrop of treatment with ICPW to assess the effectiveness of treatment and timely prediction of possible complications of pregnancy.